2014
DOI: 10.1016/j.foodhyd.2014.05.017
|View full text |Cite
|
Sign up to set email alerts
|

Production of high yield sugars from Kappaphycus alvarezii using combined methods of chemical and enzymatic hydrolysis

Abstract: The characteristics and functional properties of polysaccharides extracted from Malaysia's seaweeds have not been fully established to date. Hence, this study was carried out to produce high yield fermentable sugars from Kappaphycus alvarezii for the potential production of biotechnology products such as bioflavours. In order to achieve this objective, the effectiveness of hydrolysis process was studied by using chemical treatments, followed by enzymatic treatments. K. alvarezii were hydrolysed in different he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
27
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(31 citation statements)
references
References 22 publications
3
27
0
1
Order By: Relevance
“…Based on Table S6, our study shows a better result, with the concentration of sugars at 98.7 g/L, compared with Abd-Rahim et al (2014). The concentration of reducing sugars after combining both methods reached 49.9 g/L when EC (whole biomass) was hydrolyzed with sulfuric acid followed by enzymatic hydrolysis.…”
Section: Combination Methods For Hydrolysis At Conditions Giving Highmentioning
confidence: 69%
See 1 more Smart Citation
“…Based on Table S6, our study shows a better result, with the concentration of sugars at 98.7 g/L, compared with Abd-Rahim et al (2014). The concentration of reducing sugars after combining both methods reached 49.9 g/L when EC (whole biomass) was hydrolyzed with sulfuric acid followed by enzymatic hydrolysis.…”
Section: Combination Methods For Hydrolysis At Conditions Giving Highmentioning
confidence: 69%
“…However, j-carrageenan content cannot be easily hydrolyzed by the enzyme because of their ability to bind with water effectively, thus forming weak water gels which are very stable against enzymatic degradation. Recently, several studies reported bioethanol production from Kappaphycus alvarezii (E. cottonii) using sulfuric acid as the catalyst (Abd-Rahim et al, 2014;Hargreaves et al, 2013). Nevertheless, these methods have major drawbacks in product separation, reactor and equipment corrosion, and waste effluent treatment (Guo et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Generally, seaweeds contain large amounts of complex sulphated carbohydrates (polysaccharides) that are often extracted for use mainly in the hydrocolloid industry [8]. Each seaweed group uniquely consists of different types of complex polysaccharides serving as storage and supporting structural tissue such as the cell wall [20].…”
Section: Composition Of Sugars In Seaweedsmentioning
confidence: 99%
“…Various treatments have been used during hydrolysis of seaweed for bioethanol production. These treatments include dilute acid thermal [20,54,55], dilute alkaline thermal [15,56], enzymatic [50,57,58], thermal [55,59], ball milling [17], hydrothermal (HTT) [17] and ultrasound [60]. These are usually grouped into physical, chemical, thermal and enzymatic treatments.…”
Section: Hydrolysis Of Seaweedsmentioning
confidence: 99%
See 1 more Smart Citation